Distinct Hadean Mantle Sources of Felsic and Mafic Terranes Juxtaposed in the Paleoarchean - Arathy Ravindran; Bradley J. Peters; Klaus Mezger; Eric Hasenstab‐Dübeler; Maya J. M.; Maria Schönbächler (Geochemistry, Geophysics, Geosystems)
Abstract The short‐lived radionuclide system 146Sm‐142Nd can provide direct information about geological differentiation events in the terrestrial Hadean (>4.0 Ga) mantle. The spatiotemporal formation and evolution of crustal material that formed from different mantle domains can constrain the existing geodynamic environment in which continental crust formed and plate tectonics was initiated. The coupled 146,147Sm‐142,143Nd isotope systematics of contemporaneous felsic and mafic‐ultramafic igneous rock suites emplaced in the western Dharwar Craton (India) at ∼3.6 Ga record distinct Hadean mantle differentiation events in their source. The older mantle differentiation at 4.38−0.48+0.12 Ga ago is recorded in the felsic rock suites. The most primitive crustal representatives alone yield a differentiation age of 4.45−0.18+0.08 Ga. This early Hadean event is contemporaneous with the large silicate differentiation event recorded globally by Archean rocks. In contrast, the contemporaneous mafic‐ultramafic suites from the Dharwar Craton record a later mantle differentiation event at 4.15−0.13+0.07 Ga. Thus, distinct Hadean mantle differentiation events are preserved in coeval Archean felsic and mafic‐ultramafic igneous rock suites from a single location. The large spread in the isotope ratios in the differentiated felsic suites of the craton is likely related to the mixing of differentiated precursor material with other reservoirs prior to the formation of the first continental crust. The juxtaposition of coeval felsic and mafic crusts, each ultimately derived from mantle domains that evolved spatially and chemically separately for up to 1.1 Ga, implies the onset of lateral movement of lithospheric plates by ∼3.6 Ga.